Lithuania in Russian Epos (On the Poetics of Names) - Mitropolskaja, N. (Literatūra, 1974)
The image of the poetical name Lithuania (Lietuvos) extends far beyond historical and geographical boarders. It is an epic image of a neighbouring or even a far remote country. The image acquires aesthetic function and becomes a part of poetical formulae.